How do you use the chain rule to differentiate sqrt(-cosx)? Calculus Basic Differentiation Rules Chain Rule 1 Answer Bdub Nov 1, 2016 y'=sinx/(2sqrt(-cosx) Explanation: y= sqrt(-cosx)=(-cosx)^(1/2) y'=1/2(-cosx)^(-1/2) *sinx y'=sinx/(2sqrt(-cosx) Answer link Related questions What is the Chain Rule for derivatives? How do you find the derivative of y= 6cos(x^2) ? How do you find the derivative of y=6 cos(x^3+3) ? How do you find the derivative of y=e^(x^2) ? How do you find the derivative of y=ln(sin(x)) ? How do you find the derivative of y=ln(e^x+3) ? How do you find the derivative of y=tan(5x) ? How do you find the derivative of y= (4x-x^2)^10 ? How do you find the derivative of y= (x^2+3x+5)^(1/4) ? How do you find the derivative of y= ((1+x)/(1-x))^3 ? See all questions in Chain Rule Impact of this question 1693 views around the world You can reuse this answer Creative Commons License